Digital collections of cultural heritage of the Canary Islands: current situation and proposal for action - Núñez, María Esther; Ortiz Repiso, Virginia (Revista General de Información y Documentación, 2019)
The results obtained in a study carried out between the end of 2015 and the beginning of 2017 on the state of the heritage of the Canary Islands digitized and accessible through the Internet are presented, with a view to proposing a future regional digital library in the field of semantic web technologies. The 87 existing projects are analyzed. Most of them are led by public institutions, but with a clear disconnection between them. Many initiatives are being carried out, but this work highlights the shortcomings that exist. These lead to a clear lack of interoperability between the different initiatives, which prevents many of the projects from participating in major collective platforms such as Hispana or Europeana. It is observed that each administration walks, at a general level, in its own direction and with its own objectives and approaches, it seems that the digital dissemination of its heritage should be more a reflection of its own administrative structure than of the very idiosyncrasy of the heritage published on the network. Solutions are proposed to alleviate these deficiencies and to make a regional digital library of the Canary Islands adapted to other national and international uses a reality.